Comparative Analysis of Antibacterial Activity of Eco-Enzyme from Fruit Peel Waste against Gram-Positive and Gram-Negative Bacteria Using the Kirby–Bauer Method - Alvi Umayah; Bowo Sugiharto (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2026)
The increasing ability of bacteria to develop resistance to antibiotics highlights the urgent need for alternative antibacterial agents that are safe, affordable, and environmentally friendly. One promising option is eco-enzymes produced through the fermentation of fruit peel waste. This study aimed to compare the antibacterial activity of eco-enzymes derived from pineapple peel (Ananas comosus), dragon fruit peel (Hylocereus polyrhizus), and a mixture of both against Escherichia coli and Staphylococcus aureus. An experimental study was conducted using a post-test only control group design. The eco-enzymes were anaerobically fermented for three months and subsequently evaluated for antibacterial activity using the Kirby–Bauer disc diffusion method on Nutrient Agar (NA), with bacterial cultures prepared in Nutrient Broth (NB). Each treatment was performed in triplicate, and inhibition zone diameters were analyzed using quantitative descriptive analysis. The results showed that pineapple peel eco-enzyme produced the largest inhibition zones against S. aureus (12.5 mm) and E. coli (9.6 mm), which were classified as moderate to strong antibacterial activity according to Clinical and Laboratory Standards Institute (CLSI) criteria. In contrast, dragon fruit peel eco-enzyme exhibited no inhibitory effect on either bacterium, while the mixed eco-enzyme demonstrated weak to moderate inhibition against S. aureus (6.6 mm) and E. coli (3.7 mm). Overall, pineapple peel eco-enzyme displayed the highest antibacterial effectiveness and shows potential for development as a natural antibacterial agent derived from organic waste.